Emotions in green: unveiling the paradox of green human resource management in shaping employee conduct - Wang, Xueling; Wang, Qingjin; Hao, Jinlei; Niu, Bolin; Xu, Wenjie; Liu, Yuhan (Frontiers in Psychology, 2025)
This study examines the paradoxical dual effects of Green Human Resource Management (GHRM) in the hospitality industry. While prior comparative research has shed light on its positive impacts on organizations, the exploration of its potential adverse effects, particularly the reasons behind its paradoxical effects, is less developed. Grounded in the cognitive appraisal theory of emotion, this research analyze 407 valid survey responses from China to investigate the conditions under which GHRM leads to both benefical and detrimental organizational effects. The findings reveal that for employees with high green personal values, GHRM triggers positive emotions, thereby promoting organizational green advocacy behaviors. Conversely, for employees with lower green values, it induces negative emotions, which in turn increase workplace cheating behaviors. Theoretically, this study advances the understanding of the paradoxical nature of GHRM, particularly within the context of the hospiality sector. Practically, it offers valuable insights for implementing green management in the industry, broadening the comprehension of how corporate green management in the industry, broading the comprehension of how corporate green initiatives interact with employee values. These insights can assist the hospitality sector in adopting GHRM more effectively, enhacing environmental performance, and responding to the growing environmental concerns of customers and stakeholders.